Edge-Assisted Vehicular Networks Security. - Onieva-González, José Antonio; Ríos-del-Pozo, Rubén; Román-Castro, Rodrigo; López-Muñoz, Francisco Javier (My University, 2019)
Edge Computing paradigms are expected to solve some major problems affecting current application scenarios that rely on Cloud computing resources to operate. These novel paradigms will bring computational resources closer to the users and by doing so they will not only reduce network latency and bandwidth utilization but will also introduce some attractive context-awareness features to these systems. In this paper we show how the enticing features introduced by Edge Computing paradigms can be exploited to improve security and privacy in the critical scenario of vehicular networks (VN), especially existing authentication and revocation issues. In particular, we analyze the security challenges in VN and describe three deployment models for vehicular edge computing, which refrain from using vehicular-to-vehicular communications. The result is that the burden imposed to vehicles is considerably reduced without sacrificing the security or functional features expected in vehicular scenarios.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/29486?template=romeo
Keywords: Internet de los objetos; Redes de ordenadores - Medidas de seguridad; Internet of Things; Security; Privacy; Vehicular networks; Critical infrastructures